2018
DOI: 10.1186/s13256-018-1930-6
|View full text |Cite
|
Sign up to set email alerts
|

An epidermal cyst of the penis after distal hypospadias surgery: a case report

Abstract: BackgroundEpidermoid cyst is a benign tumor that can occur anywhere in the body but is rarely seen in the penis. Congenital and previous penile surgeries have been reported to be involved in the etiology of the disease, which is usually asymptomatic. Here we describe a case of a patient with a penile epidermoid cyst, which occurred in the circumcision line on the left side of his penis, and urethral dehiscence following hypospadias surgery.Case summaryA 3-year-old white boy who underwent primary distal hypospa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…13 Another very recent case report by Gular et al concluded that epidermal inclusion cyst as a complication of hypospadias surgery is a very rare situation and histopathological diagnosis and surgical excision is sufficient for treatment. 14 The present study results corroborate these findings.…”
Section: Discussionsupporting
confidence: 91%
“…13 Another very recent case report by Gular et al concluded that epidermal inclusion cyst as a complication of hypospadias surgery is a very rare situation and histopathological diagnosis and surgical excision is sufficient for treatment. 14 The present study results corroborate these findings.…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that these practices lead to the formation of cysts by causing traumatic implantation of the epidermis and occlusion of eccrine sweat glands and hair follicles [4,7,14]. In our series, in a case with a history of hypospadias surgery, we believe that cyst formation occurred due to penile block injection used for postoperative analgesia because the cyst was in the penile dorsum close to the penopubic junction (Figure 1 PECs are rigid, solitary, well-circumscribed, round, painless, and mobile masses that generally grow slowly [3,4,15,16]. Diagnosis is usually made using clinical findings and confirmed by histopathological examination.…”
Section: Discussionmentioning
confidence: 76%
“…Epidermoid cysts of the penis are mainly encountered in children 2 . These cysts result from implantation and proliferation of epidermal elements in the dermis.…”
Section: Discussionmentioning
confidence: 99%